Present status and future prospects of underutilized fruit tree crops in Spain - Llácer, Gerardo; Martínez-Valero, R.; Melgarejo, Pablo; Romero, M.; Toribio, F. (CIHEAM, 2023)
In Spain there are regular cultures of the 5 fruit tree species that are involved in the present work: about 20,000 ha of fig trees (Ficus carica), 3,700 ha of loquat trees (Eriobotrya japonica), about 1,000 ha of Japanese persimmon (Diospyros kaki), 2,600 ha of pomegranate (Punica granatum) and 227 ha of Barbary fig (Opuntia ficus-indica). In addition, in all cases there is a large number of scattered trees. Although the 5 species have traditionally been considered as marginal crops, all of them have a great significance in very localized situations. Because of the crisis that affects agriculture, and the need to search for new alternatives, the present trend is to intensify these cultures, a process that has progressed particularly in the case of loquat in the Alicante province. In the 4 species cited in the first place, studies have been undertaken to improve both the plant material and the commercialization.